Tashmīm Qāmus “al-Zirā‘ah” Kawasīlah Ta‘allum Al-‘Arabiyyah Li Thalabah Qism al-Tiknūlūjiyā Al-Shinā‘iyyah Al-Zirā‘iyyah Muassasn ‘Alā al- Mudawwanah al-Lughowiyyah - Suryadarma, Yoke; Fakhiroh, Alinda Zakiyatul (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2020)
The linguistic corpus is an old study in language learning that has been carried out by experts in their fields and continues to experience significant development along with the use of digital technology in the era of the industrial revolution 4.0. In learning Arabic in Indonesia, the use of the linguistic corpus is still low, as is its use in the design of bilingual Indonesian-Arabic dictionaries in various fields. In fact, the need for a bilingual Indonesian-Arabic dictionary is a necessity throughout the ages for Arabic students in Indonesia, especially students of non-native speakers. Starting from this, this paper seeks to provide an overview of the research on “Kamus Az-Ziro’ah” design, which is a bilingual Indonesian-Arabic dictionary in the field of agro-industry by using the sketchengine application as a data processing analysis based on the linguistic corpus in the preparation of vocabulary (entries and lemmas). Later, this dictionary will be used by students of the Agro Industrial Technology (TIP) UNIDA Gontor or other Arabic learners as a medium for learning Arabic. The method in this paper uses a qualitative method that describes descriptively the analysis using the Corpus Linguistic approach on design of “Kamus Az-Ziro’ah”. From this research, it is found that the design of bilingual Indonesian-Arabic dictionary using a Corpus Linguistic approach can be carried out optimally and produces the vocabulary that appears most often and is used in the agro-industry sector.